1984
DOI: 10.1111/j.1751-1097.1984.tb04616.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Polymerase Involvement in Excision Repair of Damage Induced by Solar Radiation at Defined Wavelengths in Human Fibroblasts

Abstract: Cultured fibroblasts derived from normal human skin have been irradiated at a series of monochromatic wavelengths throughout the ultraviolet region and exposed to the specific α polymerase inhibitor, aphidicolin (1 μg/ml, 2 days) prior to assay for colony forming ability. Repair of 75‐80% of the lethal damage induced by UVC (254 nm) or UVB (302 nm, 313 nm) radiation is inhibited by aphidicolin suggesting that such damage is repaired by a common α polymerase dependent pathway. Exposure to aphidicolin after irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…These may account for at least some of the DNA damage produced by sunlight. In addition, Tyrrell and Amaudruz (1984) showed that aphidicolin, which inhibits a-DNA polymerase, sensitized cells to wavelengths below 313 nm but not to wavelengths above 313 nm, suggesting different repair pathways for the damage produced by different wavelength regions. Although the current literature is somewhat confusing regarding the chromophores that are most likely involved in mammalian cell responses to the UV radiation present in sunlight, it seems likely that lesions other than, or in addition to, pyrimidine dimers are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may account for at least some of the DNA damage produced by sunlight. In addition, Tyrrell and Amaudruz (1984) showed that aphidicolin, which inhibits a-DNA polymerase, sensitized cells to wavelengths below 313 nm but not to wavelengths above 313 nm, suggesting different repair pathways for the damage produced by different wavelength regions. Although the current literature is somewhat confusing regarding the chromophores that are most likely involved in mammalian cell responses to the UV radiation present in sunlight, it seems likely that lesions other than, or in addition to, pyrimidine dimers are important.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the effects of cell exposure to more "natural" radiations, i.e. those of wavelength longer than 286 nm, recent studies have used both monochromatic (Coohill et al, 1983;Han et al, 1984;Keyse et al, 1983;Peak et al, 1985a;Peak er al., 1985b;Roza et al, 1985;Rosenstein and Ducore, 1983;Tyrrell and Amaudruz, 1984;Zelle et al, 1980;Zolzer and Kiefer. 1984;Tyrrell and Amaudruz, 1984;Zelle et af., 1980;Zolzer and Kiefer, 1984) and polychromatic sources (Erickson et al, 1980;Holmberg al., 1985;Jacobson and Krell, 1982;Patton et al, 1984;Suzuki et al, 1981;Zamansky, 1986) and even "natural" (incident on the Earth's surface) sunlight (Kantor and Ritter, 1983;Kantor and Ritter, 1984;Kantor, 1985;Parsons and Musk, 1982;Parsons and Hayward, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…oxidant role against oxidative damage (Chow, It has been shown both by epidemiologic studies in man and by animal experiments that ultraviolet (UV) radiation is involved in the induction of human skin cancer (Black and Chan, 1977;Blum, 1959;Urbach, 1979). The important wavelengths in sunlight for inducing cancer in humans are believed to be those in the UV-B (290-320 nm) region of the solar spectrum because this region most effectively produces tumors in animals (Ley et al, 1983) and induces cytotoxicity (Enninga et al, 1986;Tyrrell and Amaudruz, 1984), chromosomal aberration (Rosenstein and Rosenstein, 1985) and mutation (Collela et al, 1986;Ikebuchi et al, 1988) in cultured mammalian cells. Ellison and Childs (1981), Niggli and Cerutti (1983) and Okaichi et al (1989) have reported that pyrimidine dimers are formed by irradiation with UV-B wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…, 1974;Ellison and Childs, 1981;Rosenstein and Mitchell, 1987), such that cellular sensitivity to far U V radiation of 254 nm may not be a reliable indicator of sunlight sensitivity for a particular cell strain or directly extrapolated to the effects of environmental U V radiation exposure in humans. Tyrrell and Amaudruz (1984) showed that aphidicolin, which inhibits a-DNA polymerase, sensitised cells to far U V irradiation but not to mid and near UV wavelengths above 313 nm, suggesting different repair pathways for the damage produced by these different U V regions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that mid and near UV exposure of wavelengths longer than 320 nm produces a different spectrum of cellular DNA damage compared to germicidal UV exposure of predominantly 254 nm (Tyrrell et al, 1974;Ellison and Childs, 1981;Rosenstein and Mitchell, 1987) and that different repair pathways exist in human cells for the repair of DNA damage produced by these two different UV regions (Tyrrell and Amaudruz, 1984). Thus a cellular response to germicidal UV exposure may not be a true indicator of a cells responses to sunlight.…”
Section: Introductionmentioning
confidence: 99%